Anxiety and Motion Sickness Susceptibility May Influence the Ability to Update Orientation in the Horizontal Plane of Healthy Subjects - Alcantara-Thome, Mónica; Miguel-Puga, José A.; Jauregui-Renaud, Kathrine (Frontiers in Integrative Neuroscience, 2021)
Few studies have evaluated the influence of idiosyncrasies that may influence the judgment of space-time orientation after passive motion. We designed a study to assess the influence of anxiety/depression (which may distort time perception), motion sickness susceptibility (which has been related to vestibular function, disorientation, and to the velocity storage mechanism), and personal habits on the ability to update orientation, after passive rotations in the horizontal plane. Eighty-one healthy adults (22–64 years old) accepted to participate. After they completed an in-house general health/habits questionnaire, the short Motion Sickness Susceptibility Questionnaire, the Hospital Anxiety and Depression Scale (HADS), the Pittsburgh Sleep Quality Index, and the short International Physical Activity Questionnaire, they were exposed to 10 manually driven whole-body rotations (45°, 90°, or 135°), in a square room, with distinctive features on the walls, while seated in the normal upright position, unrestrained, with noise-attenuating headphones and blindfolded. After each rotation, they were asked to report which wall or corner they were facing. To calculate the error of estimation of orientation, the perceived rotation was subtracted from the actual rotation. Multivariate analysis showed that the estimation error of the first rotation was strongly related to the results of the orientation test. The magnitude and the frequency of estimation errors of orientation were independently related to HADS anxiety sub-score and to adult motion sickness susceptibility, with no influence of age, but a contribution from the interaction of the use of spectacles, the quality of sleep and sex. The results suggest that idiosyncrasies may contribute to the space-time estimation of passive self-motion, with influence from emotional traits, adult motion sickness susceptibility, experience, and possibly sleep quality.